DC Office of the State Superintendent of Education : turning commitment into effectiveness - Rosenthal, Jean, active 2021, (SAGE Business cases., 2021)
The case examines how Hanseul Kang turned around the organizational culture in the Office of the State of Superintendent of Education (OSSE). Before Hanseul became State Superintendent of Education in Washington DC, the OSSE had a faced a number of problems: poor morale amongst staff, different functions in conflict one another and a lack of leadership. The case outlines the measures that Kang implemented to turn the OSSE around particularly on issues related to employee morale.